Penanggulangan Tindak Pidana Korupsi Oleh Korporasi Dengan Konsep Deferred Prosecution Agreement - I Nengah Nuarta; Mochamad Sukedi (Fakultas Hukum, Universitas Warmadewa, 2025)
The objectives of combating corruption as stipulated in UNCAC 2003 are to effectively and efficiently eradicate corruption, recover assets, and build international cooperation. None of the objectives are to punish perpetrators as severely as possible. The concept of deferred prosecution agreements is marked by a shift in the principle of combating corruption from primum remedium to ultimum remedium. Based on the background described above, several issues can be formulated as follows: 1) How are corporate corruption crimes regulated in UNCAC 2003 and Indonesian positive law? 2) How does the concept of deferred prosecution agreements serve as an effort to combat corporate corruption crimes? The type of research used in this study is normative legal research. The technique of legal material analysis applied in this study is legal interpretation. The results of this study show that the regulation of corporate corruption in UNCAC 2003 and Indonesian positive law can be seen in several provisions of UNCAC 2003, namely: Article 12 paragraph (2) letter c; Article 14 paragraph (1); Article 26; Article 46 paragraph (2); Article 51; Article 52 paragraph (2). Specifically regarding the regulation of corporate liability in Article 26 of UNCAC 2003, compared to the provisions in Article 1 number 3, Article 18 and Article 20 of the PTPK Law. The formulative policy of deferred prosecution agreements in criminal acts of corruption committed by corporations in the future (ius constituendum) with the concept of deferred prosecution agreements that can be accommodated for application in Indonesia must refer to the Indonesian legal culture based on the noble values of Pancasila and adhere to the trilogy of judicial principles: simplicity, speed, and low cost.